To write a wrong - Turano, Jen (Turano, Jen. Bleecker Street Inquiry Agency, 2021)
"Daphne Beekman is a mystery writer by day, inquiry agent by night. She happily works behind the scenes, staying away from danger. But when Herman Henderson arrives on the doorstep, desperate for someone to investigate numerous attempts on his life, Daphne finds herself in the thick of a case she's determined to solve, and her heart put in jeopardy"--